Foreign Bank Entry and Credit Allocation in Emerging Markets - Kozak, Sylwester (IMF Working Papers; Working Paper ;, 2009)
We employ a unique data set containing bank-specific information to explore how foreign bank entry determines credit allocation in emerging markets. We investigate the impact of the mode of foreign entry (greenfield or takeover) on banks' portfolio allocation to borrowers with different degrees of informational transparency, as well as by maturities and currencies. The impact of foreign entry on credit allocation may stem from the superior performance of foreign entrants ("performance hypothesis"), or reflect borrower informational capture ("portfolio composition hypothesis"). Our results are broadly in line with the portfolio composition hypothesis, showing that borrower informational capture determines bank credit allocation.m.